Does independent commissioner have a role in the relationship between sustainability disclosure, debt policy, and tax avoidance? - Riska Aditya Rahma; Amrie Firmansyah (Journal of Contemporary Accounting, 2022)
This study examines the effect of sustainability disclosure and debt policy on tax avoidance. It includes an independent commissioner as a moderating variable. This study employed a quantitative method and secondary data obtained from financial reports and annual reports of companies in the consumer goods sector in Indonesia which are listed on the Indonesia Stock Exchange (IDX). Data were obtained from www.idx.co.id, www.idnfinancials.com and the company's official website. The research sample comprised 52 companies which were observed through 220 observations between 2017 and 2020. The hypothesis testing in this study was conducted by using multiple linear regression analysis for panel data. The results of this study suggest that sustainability disclosure and debt policy are negatively related to tax avoidance. Furthermore, independent commissioner does not have a moderating role in the relationship between sustainability disclosure and tax avoidance. Meanwhile, independent commissioner strengthens the negative relationship between debt policy and tax avoidance. This study indicates that the Indonesia Financial Services Authority needs to improve policies in selecting independent commissioners from listed companies in Indonesia to improve corporate governance implementation.